THE HYPOTHESES OF FLA AND CHILDREN LANGUAGE DEVELOPMENT - Rochmat Susanto (Universitas Sebelas Maret, 2017)
This article is aimed at explaining the hypotheses of FLA (First Language Acquisition) and children language development. As we know that there are many hypotheses and theories concerning about language FLA and language development as well. Therefore this article attempts to explain the most applicable hypothesis of FLA and also explain the justifications. Then this paper also explains what the sequences stages of children language development.Literally there are only three most prominent related hypotheses dealing with FLA. They are Innateness or nativism, behaviorism, and cognitivism. From those three hypotheses the author regards that the most applicable hypotheses dealing with FLA is innateness hypothesis. It explains that children automatically acquire language because they are equipped with a special language device called LAD (Language Acquisition Device) in their brain. While the other two are more appropriate to explain second language learning or SLA.Then concerning the language development of children, basically there are three main processes of language acquisition. They are phonological development, syntactical development, and semantic development.